The intonation patterns of questions in Malaysian English / Yap Tsong Shiuan - Yap, Tsong Shiuan (2016)
Since its introduction to Malaya by the British in the 18th century, the English language spoken in Malaysia has developed to become a local variety of English which we call Malaysian English (MalE). The purpose of this study is to identify and compare the intonation patterns used by MalE speakers when asking wh-questions and yes/no-questions. Twelve Malaysian speakers of the three major ethnic groups in Malaysia (Malay, Chinese and Indian) were recorded reading a list of questions and participating in an information gap activity. Analysis on the initial and final boundary tones indicates that Malaysian speakers of English almost consistently begin yes/no-questions at a level tone and end with rising tone. For wh-questions, some differing patterns emerge: Malay speakers began the questions at a level tone, ending with a falling tone, Chinese speakers had high initial boundary tone and either rising or falling final boundary tones and Indian speakers produced rising or level initial boundary tones and rising final boundary tones. From a perception test which was conducted to determine if the ethnicity of the speakers could be identified from their speech, listeners were able to identify speakers who share the same ethnicity as their own, but not the ethnicity of other ethnic groups. While certain intonation patterns distinctive to the different ethnic groups have been identified, some of these features are not reliably observable, which suggests a convergence. Further, there were more rising final boundary tones when ending wh-questions in MalE by the three ethnic groups compared to British English and American English, despite the differences. The rise of systematic linguistic patterns of MalE spoken across the three major ethnic groups supports Gut‟s (2007) Norm Orientation Hypothesis, which states that such patterns emerge when speakers of a local variety accept the endonormative rather than an exonormative norm. In other words, MalE may be shifting from the nativisation phase to the endonormative stabilisation phase of Schneider‟s (2007) theory for the development of new Englishes.